Challenges and Opportunities for Using Smartphones as Learning Media for Students of Islamic Education Study Program, State University of Jakarta - Rara, Muthiara Zahra; Liza, Haliza Hanif; Asti, Asti Siti Nur Ajijah; Riri, Rizki Ramadhan Fajrin (South Sulawesi Education Development, 2024)
The development of technology today is increasingly rapid, including the use of smartphones that make it easy for users to access anything. Smartphones have a very important role for students as a tool to facilitate the learning process and do assignments. The purpose of this study is to analyze the opportunities and challenges of students towards the use of smartphones as a learning medium for students of the Islamic Religious Education Study Program at UNJ. This research uses a qualitative method. The data collection instrument used a questionnaire with 70 respondents of Islamic Religious Education students at the State University of Jakarta. The results of this study smartphones make it easier for students to find information but smartphones can also be a challenge because it harms students such as rarely interacting with their environment, this makes it difficult for students to understand the concept of effective communication, high-level and rational thinking, and high productivity, so that their mindset becomes simple and dependence, and disrupt concentration.